Neuronavigation system in neurosurgery: Technical details and our early clinical experiences - jha, Rajiv; Khambu, Bikesh; Shrestha, Rajendra; Bista, Prakash (Nepal Journal of Neuroscience, 2021)
Introduction: Image-guided surgery is the need of time in neurosurgery. The use of neuronavigation has a significant impact on various neurosurgical procedures. We report our clinical experience and surgical techniques of neuronavigation assisted intracranial and spinal surgeries.Materials and Method: This is observational longitudinal study of 65patients who underwent surgeries using navigation system in the department of neurosurgery, National Neurosurgical Referral Center, National Academy of Medical Sciences (NAMS) Bir hospital and National Trauma Center, over the period of one and a half year. Description of Navigation techniques, its applications and surgical outcome were studied. Medtronic Stealth station 7 and Brain Lab Curve Neuronavigation system, which can be used as both frame based and frameless image guided system were employed in this study.Results: We used Neuronavigation system in 60 cases of cranial procedures and 5 cases of spinal stabilizing procedures. Among intracranial surgeries we utilized this system to effectively make bone flaps and burr holes, to detect critically located deep-seated, subcortical and skull base tumors and to operate on intra parenchymal lesions with grossly unclear margins.Neuronavigation system was used in 5 cases of spinal procedures for pedicle screw placement.Conclusion: Neuronavigation is a tool that provides numerous advantages to the neurosurgeon like more accurate planning approach, ability to use smaller approaches, higher precision for intraoperative localization of different anatomical structures and offering greater surgical safety. This technique, although apparently very complex in the beginning, becomes very user-friendly gradually and positively appreciated by everyone who uses it, after going through a relatively short learning curve.